Hackathon on Climate-Smart Agriculture (english captions) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
The Hackathon is organized to coincide with the COP20 in Lima, Peru. It seeks to develop applications that build a bridge between the scientific information generated by CCAFS and the rural population of Latin America. The group with the most outstanding submission (app) that fulfills the objectives of the competition, will be awarded a prize and the winners will present their work on December 2nd, 2014 at an event organized by CCAFS. Read more about the Hackathon in this link: https://hdl.handle.net/10568/116808